Mental health help-seeking and access to services among schooling adolescents in Selangor: A mixed-methods study / Roslaili Khairudin - Roslaili , Khairudin (2019)
Introduction: Despite the availability of mental health services, a large number of adolescents are reluctant to seek help for their mental health problems. This study aims to determine help-seeking behaviour, the factors influencing the use of mental health services as well as barriers to help-seeking for mental health problems among late adolescents in Selangor. Methods: This study employed a sequential explanatory mixed-methods approach. It was divided into quantitative and qualitative phases. In the quantitative phase, the data was collected via a cross-sectional survey using a self-administered questionnaire. The variables used in the questionnaire were identified from Andersen’s Behavioural Model of Health Services Utilisation. A total of 758 school-going adolescents aged 18-19 years completed the questionnaire. Complementary to the quantitative analyses, the qualitative phase was conducted via in-depth interviews among 22 adolescents. The study was conducted from February to August 2017. Multiple logistic regression for complex sample analysis was used to analyse quantitative data. Content analysis was applied to analyse the qualitative data. Results: Findings showed that 53.2% of adolescents had sought help from any of the services in the past 12-months regardless of their current mental health status. Of these, only 3.7% sought help from formal mental health services. Among those who sought help from any of the services, 96% sought help from informal sources. Meanwhile, of those who did not seek help from mental health services, 85.9% sought help from informal sources. Among adolescents with apparent mental health problems, 59.2% sought help from any service in the past 12-months with only 6.9% seeking help from formal mental health services. The majority of adolescents in this study preferred to seek help from family (48%) and friends (38.5%). Findings from the logistic regression analyses iv indicated that adolescents who had excellent, very good and good knowledge of the symptoms of depression (OR= 2.10, 95% CI= 1.31, 3.36), experience of depression prior to survey (OR= 1.44, 95% CI= 1.02, 2.02), were aware of the available resources (OR= 1.90, 95% CI= 1.08, 3.36), and perceived need for help (OR=1.61, 95% CI 1.12, 2,29) were more likely to seek help from formal and informal mental health services. The qualitative findings further confirmed that friends and family were the leading support sources for adolescents’ mental health problems. According to the participants, concern about being judged or labelled was the most common barrier to seeking professional help. This was followed by logistic barriers, negative experience with healthcare providers, confidentiality and trust issues, and difficulty or unwillingness to express emotion. Conclusion: The findings suggest the importance of enhancing Malaysian adolescents’ knowledge of mental health, increasing awareness of the availability of mental health resources and improving help-seeking behaviour and access to mental health services. Further efforts should be made to address the barriers and provide adolescent-friendly mental health services.